Higher Ca2+ -sensitivity of arterial contraction in 1-week-old rats is due to a greater Rho-kinase activity - Mochalov, S. V.; Tarasova, N. V.; Kudryashova, T. V.; Gaynullina, Dina; Kalenchuk, V. U.; Borovik, Anatoly S.; Vorotnikov, Alexander V.; Tarasova, Olga S.; Schubert, Rudolf (Acta physiologica, 2018)
AIM: During early post-natal development, arterial contraction depends less on Ca2+ -signalling pathways but more on changes in Ca2+ -sensitivity compared to adult animals. Whether this difference is related to Rho-kinase, one of the major players affecting Ca2+ -sensitivity, is unknown for intact vessels. Thus, we tested the hypothesis that Rho-kinase critically contributes to the higher Ca2+ -sensitivity of contraction in intact arteries of 1-week-old rats. - METHODS: We studied 1-week-old, 4- to 5-week-old and 10- to 12-week-old rats performing isometric myography, Ca2+ -fluorimetry and Western blotting using intact saphenous arteries and arterial pressure measurements under urethane anaesthesia. - RESULTS: In 10- to 12-week-old rats, methoxamine (MX) produced vasoconstriction associated with an increase in [Ca2+ ]i and Ca2+ -sensitivity. In contrast, in 1-week-old rats these contractions were accompanied only by an increase in Ca2+ -sensitivity. All MX-induced effects were reduced by the Rho-kinase inhibitor Y-27632; this reduction was complete only in 1-week-old rats. The Rho-kinase specific site Thr855 on MYPT1 was increasingly phosphorylated by MX in vessels of 1-week-old, but not 10- to 12-week-old rats; this effect was also inhibited completely by Y-27632. The Rho-kinase inhibitor fasudil in a dose not affecting the pressor response to MX in 4- to 5-week-old rats reduced it considerably in 1-week-old rats. - CONCLUSION: Our results suggest that the higher Ca2+ -sensitivity of arterial contraction in 1-week-old compared to 10- to 12-week-old rats is due to a greater Rho-kinase activity. Constitutively active Rho-kinase contributes to MX-induced contraction in 10- to 12-week-old rats. In 1-week-old rats, additional Rho-kinase activation is involved. This remodelling of the Rho-kinase pathway is associated with its increased contribution to adrenergic arterial pressure responses.
Gesehen am 30.04.2020
Im Titel ist "2+" hochgestellt